2015
DOI: 10.1007/s10539-015-9500-4
|View full text |Cite
|
Sign up to set email alerts
|

Schrödinger’s microbe: implications of coercing a living organism into a coherent quantum mechanical state

Abstract: Consideration of the experimental activities carried out in one discipline, through the lens of another, can lead to novel insights. Here, we comment from a biological perspective upon experiments in quantum mechanics proposed by physicists that are likely to feasible in the near future. In these experiments, an entire living organism would be knowingly placed into a coherent quantum state for the first time, i.e. would be coerced into demonstrating quantum phenomena. The implications of the proposed experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In 2009, Romero-Isart et al [25] proposed to optically trap a living microorganism in a high-finesse optical cavity in vacuum to create a superposition state. That paper increased our hope to experimentally study the quantum nature of living organisms [1,26,27]. Meanwhile, Li et al demonstrated optical trapping of a pure silica microsphere in air and vacuum [28], and cooled its center-of-mass motion from room temperature to about 1.5 mK in high vacuum [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, Romero-Isart et al [25] proposed to optically trap a living microorganism in a high-finesse optical cavity in vacuum to create a superposition state. That paper increased our hope to experimentally study the quantum nature of living organisms [1,26,27]. Meanwhile, Li et al demonstrated optical trapping of a pure silica microsphere in air and vacuum [28], and cooled its center-of-mass motion from room temperature to about 1.5 mK in high vacuum [29].…”
Section: Introductionmentioning
confidence: 99%
“…Our proposal also works for viruses. Since many biologists do not consider viruses as living organisms [27], we focus on small bacteria in this paper. Our proposal has several advantages.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is increasing evidence that the ways the brain (Wendt 2015), human societies (Zohar and Marshall 1995), and economic systems (Orrell 2018) work is often reminiscent of quantum physical phenomena. This highlights synergies that can be exploited for genuinely novel interdisciplinary research (Bull and Gordon 2015).…”
Section: Introductionmentioning
confidence: 92%
“…It is increasingly recognized that the adoption of quantum analogies in classical systems has potential to inspire novel interpretations of their dynamics that are not at odds with classical logic (Wendt 2015, Orrell 2018). In the broadest sense, this suggests that the logics of a quantum and classical world are reconcilable and that ultimately current theories can be advanced through the cross-fertilization of both logics (Bull and Gordon 2015). This paper attempts such unification by showing that quantum superposition can inspire discussions about eco-evolutionary theories.…”
Section: Introductionmentioning
confidence: 95%
“…With the help of a superconducting circuit, the state of a living microbe may also be teleported to another microbe [12]. It was proposed that a microbe in a quantum coherent state would represent a new category of cryptobiosis [13]. Meanwhile, some organisms seem to be able to harness quantum coherence in biological processes, such as photosynthetic light harvesting and avian magnetoreception, to gain a biological advantage [14,15].…”
Section: Introductionmentioning
confidence: 99%